Effect of rock bridge length on fracture and damage modelling in granite containing hole and fissures under cyclic uniaxial increasing-amplitude decreasing-frequency (CUIADF) loads. (May 2022) - Wang, Y.; Yang, H.N.; Han, J.Q.; Zhu, C.
Highlights: Cyclic uniaxial increasing-amplitude decreasing-frequency (CUIADF) loads on pre-flawed rock. Rock bridge length affects strength, volumetric deformation AE b-value and failure modes. A new damage variable is defined using AE accumulative energy and an inverted "S" shaped damage evolution model was proposed. CT images highlight the coalescence pattern and three coalescence modes were identified. Abstract: Rock mass is often encountered with complicated stress disturbance, the cyclic or fatigue loading path with fixed loading frequency and amplitude are widely performed. To date, however, rock instability induced by cyclic uniaxial increasing-amplitude decreasing-frequency (CUIADF) loads was not well understood. In this work, granite samples containing a circular hole and two fissures with different rock bridge length were used to conduct CUIADF loading tests. The fatigue strength, deformation, AE output activities, damage propagation and crack coalescence were comprehensively investigated. Testing results show that the fatigue strength, volumetric deformation and fatigue lifetime increase with increasing rock bridge length. The AE-b value decreases as cyclic number grows and it is relatively large for rock having high rock bridge length. A new damage variable is defined using AE accumulative energy and an inverted "S" shaped damage evolution model was proposed to describe rock damage propagation in the entire process. Moreover, three failure modes of single tensile coalescence, single shear coalescence and double shear coalescence were revealed from the reconstructed CT images. It is suggested that the rock bridge length impacts the rock instability a lot, and the interactions between the hole and fissure are the weakest for a sample with long rock bridge.